On the Margins of Urban South Korea : Core Location as Method and Praxis - Hae, Laam; Song, Jesook, 1969-; Project Muse. (London : University of Toronto Press, 2019)
"On the Margins of Urban South Korea, seeks to provide rich and illuminating accounts of key sites of urban, national, and transnational development in contemporary South Korea. It is an outcome of long-term collaboration and dialogue among interdisciplinary Korean Studies scholars from architecture, anthropology, and geography. The seven key sites are the Education City Project in Jeju; the Chinatown Project in Incheon; Saemaul Undong(New Village Movement)in Pohang; Alternative Korean Wave in Bongcheon-dong, Seoul; Pine Tree Hill Neighbourhood Activism in a southern port city; sites of struggles against greenbelt deregulation in the Seoul Metropolitan Region; and the garment worker movement in Changshin-Dong, Seoul. The volume offers an original focus on key sites or, what the editors and contributors call core locations, and aims to articulate the significance of knowledge based in a particular location. It is inspired by two inter-connected notions: "core location (haeksim hyunjang)," a place with the lived experience of multiple layers of marginality in colonial history with an emphasis on the reseacher's praxis and rootedness in the location; and "Asia is Method," a means of thinking about an area, especially the non-western, not simply as an object of western interest but as a tool to generate frameworks that enable decolonization of epistemological hegemony. This volume aims to further develop the relevance of core location and Asia as Method in social science, targeting both an Anglophone readership and an audience in East Asia."--
Description based on print version record.
Keywords: POLITICAL SCIENCE / World / Asian; Sociology, Urban; Knowledge, Sociology of; Decolonization; Community development, Urban; sociology of knowledge; Sociologie de la connaissance; Decolonisation -- Coree du Sud; Sociologie urbaine -- Coree du Sud; Developpement communautaire urbain -- Coree du Sud; Knowledge, Sociology of; Decolonization -- Korea (South); Sociology, Urban -- Korea (South); Community development, Urban -- Korea (South); Korea (South); Electronic books